(untitled) (Journal of Contemporary Dental Sciences, 2026)
Background: Zygomaticomaxillary complex (ZMC) is an important functional landmark of the midface. Due to its intrinsically prominent convexity it becomes most vulnerable to injury. ZMC fractures commonly destroy the integrity of the orbital skeleton, and are frequently complicated by injury to the eye. So the optimum ophthalmic evaluation of the patient who sustained ZMC fractures is mandatory to prevent any further ocular complications. This study was carried out to evaluate the ophthalmic complications associated with ZMC fractures to provide sufficient information for better treatment planning and management. Method: This observational type of study was conducted in Oral and Maxillofacial Surgery Department, Dhaka Dental College Hospital during the period between February2021 to January 2022. Twenty five patients who fulfilled the criteria were selected by purposive sampling. All the patients were observed by the same group of oral and maxillofacial surgeons and ophthalmologists. Results: Out of 25 patients mean age of the patients was 30.8±10.1 years. Majority 92% of the patients were male and 8% were female. Among all, 68% had fracture due to road traffic accident, 12% had fracture due to fall from one level to another and 12% of the patients had fracture due to assault. Besides, 4% said fall on a level surface and 4% said other different type of causes for fracture. Ninety-two percentage of the patients had developed Subconjunctival hemorrhage followed by 32% had Reduced visual acuity, 20% had developed Diplopia, 16% had developed Enophthalmos, 12% had Corneal injury and 4% had developed Loss of vision. Conclusion: All traumas to the face, particularly above the level of the mouth, require a careful eye examination. Considerable care should be taken in all patients who may have sustained eye injuries in association with ZMC fractures for the proper management to prevent any blinding complications. J. Contemp. Dent. Sci. 2026;14(1):18-22